Sonoporation generates downstream cellular impact after membrane resealing - Xinxing Duan (Nature Portfolio, 2021)
Abstract Sonoporation via microbubble-mediated ultrasound exposure has shown potential in drug and gene delivery. However, there is a general lack of mechanistic knowledge on sonoporation-induced cellular impact after membrane resealing, and this issue has made it challenging to apply sonoporation efficiently in practice. Here, we present new evidence on how sonoporation, without endangering immediate cell viability, may disrupt downstream cellular hemostasis in ways that are distinguished from the bioeffects observed in other sonicated and unsonoporated cells. Sonoporation was realized on HL-60 leukemia cells by delivering pulsed ultrasound (1 MHz frequency, 0.50 MPa peak negative pressure; 10% duty cycle; 30 s exposure period; 29.1 J/cm2 acoustic energy density) in the presence of lipid-shelled microbubbles (1:1 cell-to-bubble ratio). Results showed that 54.6% of sonoporated cells, despite remaining initially viable, underwent apoptosis or necrosis at 24 h after sonoporation. Anti-proliferation behavior was also observed in sonoporated cells as their subpopulation size was reduced by 43.8% over 24 h. Preceding these cytotoxic events, the percentages of sonoporated cells in different cell cycle phases were found to be altered by 12 h after exposure. As well, for sonoporated cells, their expressions of cytoprotective genes in the heat shock protein-70 (HSP-70) family were upregulated by at least 4.1 fold at 3 h after exposure. Taken altogether, these findings indicate that sonoporated cells attempted to restore homeostasis after membrane resealing, but many of them ultimately failed to recover. Such mechanistic knowledge should be taken into account to devise more efficient sonoporation-mediated therapeutic protocols.